2015
DOI: 10.1097/olq.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors and HIV/Syphilis Testing Among Transgender Individuals in China

Abstract: Background HIV and syphilis are disproportionately common among transgender individuals globally, yet few studies have investigated transgender HIV/syphilis risk and testing in low and middle-income nations. We conducted an online survey of men who have sex with men (MSM) and transgender individuals to examine sexual behaviors, and HIV/syphilis testing in China. Methods We recruited MSM and transgender individuals from two-major Chinese lesbian, gay, bisexual, and transgender (LGBT) web platforms. Chi-square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
2
35
1
Order By: Relevance
“…Second, lack of screening and poor service delivery have contributed to the epidemic. For example, one survey from 2013 revealed that only about 30% men who have sex with men (MSM) reported ever having tested for syphilis, despite a syphilis prevalence of 9%13. Limited screening and other related services may miss a large number of syphilis patients that need to be diagnosed and treated, resulting in a larger proportion of preventable early syphilis cases progressing to neurosyphilis or other types of tertiary syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, lack of screening and poor service delivery have contributed to the epidemic. For example, one survey from 2013 revealed that only about 30% men who have sex with men (MSM) reported ever having tested for syphilis, despite a syphilis prevalence of 9%13. Limited screening and other related services may miss a large number of syphilis patients that need to be diagnosed and treated, resulting in a larger proportion of preventable early syphilis cases progressing to neurosyphilis or other types of tertiary syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the government has significantly expanded surveillance efforts among MSM in response to the rapid spread of HIV in this key population [9]. Yet, several systematic reviews suggest that still only half of MSM have ever tested for HIV [10][11][12]. In addition, syphilis test uptake is poor in China [11], which is concerning given the rise in HIV and syphilis co-infections among Chinese MSM [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, several systematic reviews suggest that still only half of MSM have ever tested for HIV [10][11][12]. In addition, syphilis test uptake is poor in China [11], which is concerning given the rise in HIV and syphilis co-infections among Chinese MSM [13,14]. The Chinese Centers for Disease Control and Prevention (CDC) offer free HIV testing at voluntary counselling and testing sites [15].…”
Section: Introductionmentioning
confidence: 99%
“…11 There is limited data on the burden of HIV and HIV-related risk behaviours among Chinese TG individuals. The only paper focused on this Chinese demographic reported elevated risk of HIV infection compared with MSM; 12 however, the specific risk factors are still unknown. Additional research is needed to characterise the demographics, behaviours and preferences on TG individuals in China.…”
Section: Introductionmentioning
confidence: 99%